Long-term use of solifenacin in pediatric patients with overactive bladder: Extension of a prospective open-label study - Nadeau, Geneviève (Canadian Medical Association, 2014)
INTRODUCTION: We evaluate the efficacy and safety of solifenacin to treat incontinence in children with non-neurogenic (DO) or neurogenic detrusor overactivity (NDO) refractory to oxybutinin or tolterodine. METHODS: We updated and extended our previously published non-randomized uncontrolled study on open-label use of adjusted-dose regimens of solifenacin (1.25–10 mg) in children with refractory incontinence. The follow-up included voiding diaries, post-void residuals, urine cultures, ultrasounds and urodynamic studies. Clinical data were updated as of September 2012. Subjective improvement was assessed with the Patient Perception of Bladder Condition (PPBC) scale. The primary end point was efficacy toward continence and secondary end points were tolerability and safety. RESULTS: Overall, 244 patients (112 girls, 132 boys) were enrolled; 53 with NDO and 191 with DO. Minimal follow-up was 5 months, the mean duration of treatment was 21.0 months and the mean age at initiation was 9.2 years. Urodynamic capacity improved from 145 ± 76 mL to 339 ± 152 mL and the amplitude of uninhibited contractions decreased from 66 ± 26 to 20 ± 20 cmH(2)O (p < 0.0001). The overall success rate is 91%, and more specifically 94% for non-neurogenic and 79% for neurogenic, which is significantly different (p = 0.013). Twenty-three patients discontinued treatment for unsatisfactory clinical response or bothersome side effects. No side effects were reported by 175 patients, mild by 46, moderate by 9, and 14 withdrew due to their side effects. Ten patients developed post-void residuals of ≥20 mL. CONCLUSION: Although higher in the non-neurogenic group, high subjective and objective success rates were maintained over a longer follow-up with an adjusted-dose regimen of solifenacin to treat pediatric NDO or DO refractory to oxybutynin or tolterodine. Moreover, we found acceptable tolerability and safety profiles.